Technological Mindset for Young Generation in Transportation Industry - Pane, Zulfikar Ikhsan; Simatupang, Rosida; Murtiharso, Yosaphat Danis; Nuraryo, Imam (Asian Journal of Community Services, 2024)
Technological innovation in transportation firms is currently supported by presence of directors with engineering / technology education background and younger generation as audience for this community service activity because they should give motivation and awareness that a technological mindset is needed to achieve success. They should equip themselves not only with formal education but also knowledge about technology to become top level carrier. This can be done through bootcamps, training and others. This service activity was carried out through a seminar at National Leader Forum event organized by KAPPIJA 21, various universities and the South Sumatra Provincial Government. As a result, students get enlightened to start looking for their character and passion when starting a career embedded with technology.